The Development of English Learning Media Based a Bilingual an Animation Video for Students at Man Dompu - Indah Afrianti; Nur Wahyuni; Nadia Kasogi (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2025)
This study aims to develop learning media based on bilingual animation video for Past Experience material and to determine the effectiveness and feasibility of this media. The research method used is R&D which has been modified into seven stages, namely Research and Data Collection, Planning and Data Collection, Initial Product Form Development, Field Trial, Revision, Validation, Product Revision. The results in this study, the effectiveness of this learning media can be seen from the acquisition of pretest and posttest scores, namely pretest of 11% and posttest of 42%, which is the average value obtained from the number of students who reach the KKM. Then presented using a formula and from the calculation which means that forty-two percent of students have achieved the KKM score after using the media that has been developed by the researcher. The bilingual animated video-based learning media developed in this study was categorized as "very feasible". The assessment was obtained from the product validation results obtained by the validator, namely media experts with the results obtained as much as 88%, material experts with a score of 96% then linguists with a score of 88%.